Short-Time Scale Dynamics in the Responses to Multiple Stimuli in Visual Cortex - Gawne, Timothy (Frontiers in Psychology, 2011)
Many previous studies have used the presentation of multiple stimuli in the receptive fields (RFs) of visual cortical neurons to explore how neurons might operate on multiple inputs. Most of these experiments have used two fixed stimulus locations within the RF of each neuron. Here the effects of using different positions within the RF of a neuron were explored. The stimuli were presented singly at one of six locations, and also at 15 pair-wise combinations, for 24 V2 cortical neurons in two macaque monkeys. There was considerable variability in how pairs of stimuli interacted within the receptive field of any given neuron: changing the position of the stimuli could result in enhancement, winner-take-all, or suppression relative to the strongest response to a stimulus presented by itself. Across the population of neurons there was no correlation between response strength and response latency. However, for many stimulus pairs the response latency was tightly locked to the shortest response latency of any single stimulus presented by itself independent of changes in response magnitude. In other words, a stimulus that by itself elicited a relatively long latency response, could affect the magnitude of the response to a pair of stimuli, but could not change the latency. A model is proposed whereby changes in response magnitude that do not result in changes in response latency reflect rapid feed-forward processing mechanisms, and these rapid mechanisms can suppress slower, longer time-constant processing mechanisms. These results may provide constraints on the development of models of cortical information processing.